Manufacture of Nanocellulose from Red Onion Peel Waste Using Acid Hydrolysis Method with Variation of H2SO4 Concentration - Shabrina, Shabrina Yakosati; Manurung, Posman; Suciyati, Sri Wahyu; Karo, Pulung Karo (Departement of Physics, Faculty of Mathematics and Natural Sciences, University of Lampung, 2025)
The manufacture of nanocellulose from red onion peel waste has been carried out using the acid hydrolysis method using H2SO4. This study aims to determine the effect of variations in the concentration of H2SO4 on the size of nanocellulose crystallites from onion peels and the surface morphology of nanocellulose from onion peels. The manufacture of nanocellulose was carried out in three stages, namely delignification using 10% NaOH to remove lignin and hemicellulose, bleaching using 10% H2O2 for bleaching and isolation of nanocellulose using H2SO4. The variation of H2SO4 used is 5; 10; 15 and 20%. The characterizations used are XRD (X-Ray Diffraction) and SEM (Scanning Electron Microscopy). The results of XRD characterization showed that the crystalline phase contained at the highest diffraction peak and the optimum concentration of H2SO4 to make nanocellulose from onion peel was 20%. The results of SEM characterization showed that the morphology of the onion peel nanocellulose was still united to form bundles or agglomerates.